Potential of local wisdom as an effort to prevent damage to forest resources - Kevin Aditia; Endah Febri Setiya Rini; Predy Siswanto; Jiantika Rahmawati; Laili Hidayani; Ziyana Walidah Razak; Febri Tia Aldila (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Deforestation is a problem that often occurs in forest resources and has an impact on human life. This study aims to analyze the potential of local wisdom of indigenous peoples in efforts to prevent deforestation. Forest resources that have an important role in supporting the lives of living things are threatened by the very high rate of deforestation. Government efforts to reduce the rate of deforestation are still less than optimal, as evidenced by the very dynamic rate of deforestation. Therefore, efforts need to be made to reduce the rate of deforestation by involving indigenous peoples through their local wisdom. The method used in this study uses a qualitative research with a library research method to contain the research results. The results of the analysis show that deforestation is influenced by the ease of obtaining concession permits to utilize forest resources without management. Local wisdom of indigenous peoples has great potential in reducing the rate of deforestation based on perspectives, rules, and sustainable use of forest resources.